2015
DOI: 10.1097/md.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Severity-Specific Neuronal Degenerative Network in Charcoal Burning Suicide-Related Carbon Monoxide Intoxication

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Studies on delayed neurologic or neuropsychiatric syndrome revealed that CO intoxication from charcoal-burning resulted in the diffuse demyelination in the brain 15. One study found that the fronto-insular-caudate areas represented the target degenerative network in CO intoxication 25. The decrease in the gray matter volume in the bilateral basal ganglia, left postcentral gyrus, and left hippocampus is also correlated with the decreased perceptual organization and processing speed function in these patients 54 55.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on delayed neurologic or neuropsychiatric syndrome revealed that CO intoxication from charcoal-burning resulted in the diffuse demyelination in the brain 15. One study found that the fronto-insular-caudate areas represented the target degenerative network in CO intoxication 25. The decrease in the gray matter volume in the bilateral basal ganglia, left postcentral gyrus, and left hippocampus is also correlated with the decreased perceptual organization and processing speed function in these patients 54 55.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study found that the fronto-insular-caudate areas represented the target degenerative network in the CO intoxication. 25 Therefore, we hypothesize that CO intoxication in patients with suicide attempts would also be associated with dementia, and we conducted this study to clarify whether coal-burning suicide attempts would be associated with subsequent dementia.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients and controls were right handed and gave written informed consent to take part. Clinical diagnosis in both patients and controls was determined after a detailed history, neurologic examination, 1-h neuro-psychological battery (Chang et al, 2016a ), laboratory screening, and visual inspection of a 3.0-tesla brain magnetic resonance imaging (MRI; Chen et al, 2015 ). Patients diagnosed with fronto-temporal lobar degeneration met the Neary criteria (Neary et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…From neuroimaging analysis, diffuse white matter (WM) damages (Sohn et al, 2000 ; Chang et al, 2011 ) and deep gray matter (GM) injuries in the globus pallidus or basal ganglia (Klawans et al, 1982 ; Pulst et al, 1983 ; Lee et al, 2010 ) were reported. Among these seemingly unrelated areas, we recently validated that the fronto-insular-temporal brain areas represented functional network that underwent neurodegenerative processes, while the spatial extents of injury are highly predictive of the cognitive severity (Chen et al, 2015 ).…”
Section: Introductionmentioning
confidence: 98%